Konsep Hukuman dan Ganjaran dalam Al-Qur’an dan Hadits - Dedi Efendi; Charles (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
This research was conducted because it was motivated by the teacher's frustration in applying the reward and punishment method in the educational process between enforcing discipline, increasing achievement and all efforts to achieve educational goals. Between a good cause and the issue of violation of the human rights of children. Conceptually in the Qur'an and Hadith as a guide for asasi in the life of Muslims and the applicable laws and regulations very clearly provide signs for the implementation of the method of reward and punishment in the educational process. A teacher should not hesitate to apply it in the educational process. There is no need to overdo it without being able to control yourself, nor do you need to be afraid to apply it because it is considered a violation of human rights. It is precisely by applying the methods of reward and punishment appropriately, such as eating the right dose of medicine, that it will usher in education achieving its noble goal. Appreciation is given if the student is able to show an achievement that he was previously unable to do so that for him it is of educational value. On the contrary, punishment is given when the student shows an offence that he was previously unaccustomed to commit, so that when given the punishment makes him realize that he has committed a mistake. This research is a literature research with a qualitative approach